PELATIHAN PENULISAN SURAT-MENYURAT KEDINASAN APARATUR PEMERINTAH DESA CIBADUNG, KECAMATAN GUNUNG SINDUR, BOGOR - Lisa Novia; Nur Rachmah Wahidah; Riri Oktarini (Jurnal Pengabdian Sosial, 2023)
ABSTRACTThe purpose of this Community Service activity is to provide knowledge and understanding to village staff / apparatus at the Cibadung Village Office, Gunung Sindur District, Bogor Regency.  The results of this counseling are expected to be applied by village officials in carrying out their duties of organizing village government, implementing village development, community development and empowering village communities with full integrity, responsibility, and dedication in service. Keywords: Correspondence, Apparatus